If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4(x-2)=9(x+5)
We move all terms to the left:
4(x-2)-(9(x+5))=0
We multiply parentheses
4x-(9(x+5))-8=0
We calculate terms in parentheses: -(9(x+5)), so:We get rid of parentheses
9(x+5)
We multiply parentheses
9x+45
Back to the equation:
-(9x+45)
4x-9x-45-8=0
We add all the numbers together, and all the variables
-5x-53=0
We move all terms containing x to the left, all other terms to the right
-5x=53
x=53/-5
x=-10+3/5
| 2=7x-3x | | (=5x+11) | | 6x2−15x−9=0 | | 5=7x-3x^2 | | 5=7x-3x^{2} | | 4x-11+2x+17=180 | | 3x10x+5=5x+17 | | 98.68x+21.6-6.23x=2.3x+17 | | 3x-14+12x-1=180 | | -1.2(2x+5)=7x | | (2^x)(5^x+2)=25000 | | 49x=+96-32=23 | | x+1=9x+25 | | x/9+2=4.8 | | 9(a+1)+2=11 | | x-6+124=180 | | t+4/6=3/2 | | 7.5x=1000 | | x^2−14x=−47 | | 13x-9=10x+20 | | 2y^+4y+20=0 | | 4x2-5=59 | | 3(k+4)=21 | | 6x+(4x+2)=86 | | 5x+3+2x=59 | | 8/r=12 | | 6n–5+n=2(4n–7)–n | | 29=4+5•x | | –3+9s+2s=–10+4s | | (4+3x-1)/2=9 | | 3x-+1=7x-19 | | 18-7n=-3 |